Diseases of the nervous system clinical neuroscience and therapeutic principles - Asbury, Arthur K. 1928- (Cambridge University Press, 2002)
The third edition of a neurology classic, this two-volume text is the most comprehensive neurology reference available. It encompasses the basic neuroscience and clinical features of the full range of neurological disorders, written by leading international experts in the field. Disease mechanisms are reviewed comprehensively, with particular relevance to the principles of therapy. Sections cover the general principles of neurological disease, disorders of higher function, motor control, special senses, spine and spinal cord, bodily function, headache and pain, neuromuscular disorders, epilepsy, cerebrovascular disorders, neoplastic disorders, autoimmune disorders, disorders of myelin, infections, trauma and toxic disorders, degenerative disorders, and neurological manifestations of systemic conditions. Each section, under the direction of one of the distinguished editors, is a text-within-a-text, offering the most reliable account of its topic currently available. Current, comprehensive and authoritative, this is the definitive reference for neurologists, neurosurgeons, neuropsychiatrists, indeed everyone with a professional or research interest in the neurosciences